Methanol production from steel-work off-gases and biomass based synthesis gas - Ekbom, Tomas; Hulteberg, Christian; Grip, Carl-Erik; Larsson, Mikael; Lundgren, Joakim; Nilsson, Leif; Tunå, Per (Luleå tekniska universitet, Energivetenskap, 2012)
The main objective has been to describe different cases of the methanol production from steel-work off gases (Coke oven gas and Basic oxygen furnace gas) and biomass based synthesis gas. The SSAB steel mill in the town of Luleå, Sweden has been used as a basis to analyze four different methanol production cases.The studied biomass gasification technology is based on a fluidized bed gasifier unit, where the production capacity is determined from case to case coupled to the heat production required to satisfy the local district heating demand. Critical factors are the integration of the gases with availability to the synthesis unit, to balance the steam system of the biorefinery and to meet the district heat demand of Luleå.For each case, the annual production potential of methanol, the overall production efficiencies and the effects on the total steel plant have been estimated. Godkänd; 2012; Bibliografisk uppgift: Paper ID: ICAE2012-A10512; 20121127 (joakim)